Disrupt yourself: how to turn a crisis into an opportunity - Leyman, Elke (Henry Stewart Talks, 2021)
Crises and opportunities on the macro-level, Crises and opportunities on the micro-level, Crises and opportunities on the meso-level, Three fundamental transitions in society, economy and power, Act and be (what one does vs. who they are)